Implementation of GRI Standards in the Sustainability Reports of Plantation Sector Companies Listed on the Indonesia Stock Exchange (IDX) - Apriwandi; Ade Agustina Fahria (JFBA: Journal of Financial and Behavioural Accounting, 2022)
The sustainability report is one of the business strategies to increase investor confidence through specific disclosure items. This paper is written with the aim of disclosing the application of GRI Standards in sustainability reports of plantation companies listed on the IDX. The sample companies in this paper are 15 companies with the object being the 2021 plantation company sustainability report. The results of the analysis show that the disclosure of the GRI Standards implementation in plantation companies listed on the BEI is an average of 51.74% with an average number of disclosures of 73, 47 items are in the Partially Applied category. The largest average disclosure is on universal standards by 69.77%, environmental specific topics by 43.53%, social by 39.83% and economic by 32.36%. PT. Sampoerna Agro Tbk. is the company with the highest disclosure of 113 disclosure items or 79.58% in the Well Applied category. While the company that made the least disclosure in 2021 was PT. BISI International Tbk. with 41 disclosure items or 28.87% of the 142 items that must be disclosed are in the Limited Disclosure category. These results indicate that the application of GRI Standards is still relatively low so special attention is needed from plantation companies to be able to increase disclosure items in the following year considering that the impact on the company's operational activities is quite large on the economy, environment and social environment around the company's location.